Cloning, purification and characterization of a novel cold-adapted GDSL esterase from Photobacterium sp. J15 - Shakiba, Mehrnoush Hadaddzadeh (2014)
The studies of characteristics of cold-adapted enzymes have become a growing interest for researchers as these enzymes have a range of structural properties that confer a high level of flexibility, low-activation enthalpy, low-substrate affinity, and high specific activity at low temperatures compared to thermostable homologs. These features can be extremely useful in various applications such as detergent additives, textile and food industry, and bioremediation. These enzymes are both innovative and invaluable. Therefore, due to these important applications, a cold adapted esterase from family II of bacterial classification (GDSL family) was chosen to clone, purify and characterize. In current study, a novel cold-adapted GDSL esterase was isolated from Photobacterium sp. strain J15. The open reading frame (ORF) of the GDSL esterase J15 was 1044 bp in length coding for 347 amino acids with 19 amino acid residues predicted as signal peptide. The mature GDSL esterase gene was amplified by PCR and then cloned into pET-32b(+) expression vector and expressed as a His-tagged fusion protein. Due to three Leu, one Arg, and one Ile rare codons in the GDSL esterase, the recombinant plasmid was transformed into E. coli strain Rosettagami(DE3)pLysS expression host to enhance the expression of the GDSL esterase. To optimize over-expression of GDSL esterase J15, parameters such as inducer, temperature and induction time were taken into consideration. A final esterase activity of 4.318 U/ml was detected when the recombinant E. coli culture was induced with 0.1 mM IPTG at 20 °C for 16 h. The His-tagged recombinant GDSL esterase was purified in two steps chromatography; affinity chromatography using Cobalt Sepharose resin and ion exchange (IEX) chromatography using Q-Sepharose resin. After the first purification step, Trx-tag was removed from the recombinant GDSL esterase using thrombin. The protein yield from the first purification step and the final step was 57.4% and 38.5%, respectively. The purified GDSL esterase is highly active at 20 °C and pH 8. It has a half-life of 5 h at 10 °C. The activity of the enzyme was increased when added with Mg2+, Ca2+, Sr2+, Fe3+, Tween-20, Tween-60, Tween-80, Triton-100, DTT and β- mercaptoethanol. However, SDS, EDTA and PMSF inhibited the enzyme activity. In addition, the enzyme activity was increased when 1.5 M of NaCl was added to the enzyme preparation. Gene analysis of GDSL esterase showed that GDSL esterase J15 is belonged to the members of SGNH hydrolase superfamily with 31% identity with Fischerella sp. JSC-11. In the predicted model of GDSL esterase, Ser31, Asp321, and His324 were situated in close proximity, most probably representing the active site of the enzyme. Therefore, the study of the GDSL esterase J15 revealed that the enzyme is a novel cold-adapted esterase from family II with high specific activity at low temperature and other specific characteristics.